PENGARUH PEMBERIAN IMUNOMODULATOR JINTAN HITAM (Nigella sativa) TERHADAP TITER ANTIBODI AVIAN INFLUENZA dan NEWCASTLE DISEASE PADA BROILER JANTAN - Dwi Prasetyo; Purnama Edy Santosa; Madi Hartono; Muhammad Mirandy Pratama Sirat (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2021)
This study aimed to determine the effect of giving black cumin (Nigella sativa) as an immunomodulator on Avian Influenza (AI) and Newcastle Disease (ND) antibody titers in male broilers. This study was conducted in December 2019--January 2020 at the Laboratory of Integrated Field, Faculty of Agriculture, University of Lampung. Analysis of antibody titers was carried out at the Laboratory of Virology, Veterinary Disease Investigation Center Region Lampung. This study used a Completely Randomized Design with four treatments and three replications namely drinking water without Nigella sativa (P0), drinking water with 36 mg/kg BW/day Nigella sativa (P1), drinking water with 72 mg/kg BW/day Nigella sativa (P2), and drinking water with 144 mg/kg BW/day Nigella sativa (P3). The results of this study showed that administration of Nigella sativa had no significant effect on antibody titer of AI, but had significant effect on antibody titer of ND and administration 72 mg/kg BW/day of Nigella sativa was the best in increasing the antibody titer of ND in male broilers. Keywords: Avian Influenza, Black cumin, Male broiler, Newcastle Disease, Titer antibody